Future Tourist Behavioral Model Based on Perceived Value and Culinary Experience - Fahmi Muhamad Rizky; Muhammad Rifqi Rahmandika Hilmi; Afghani Mahmuda Bahreisy (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
This study aims to develop and test a model of future tourist behavior based on perceived value and the type of culinary experience obtained when visiting legendary restaurants in Bandung City. Culinary tourism is no longer merely regarded as a consumptive activity but also as a cultural experience that can foster tourist loyalty. In this study, perceived value is examined through two main dimensions: food experience value (authenticity and sensorial experience) and culinary destination value (service, atmosphere, price, spatial layout, and historical value). Meanwhile, the types of culinary experiences are classified into generic and whole experiences. The research method employed is a quantitative approach using a survey technique involving 200 respondents, with data collected through a Likert-scale questionnaire. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The results show that perceived value and type of culinary experience have a positive and significant effect on tourists’ future behavior, measured by revisit intention and recommendation to others. However, the moderating effect of the type of culinary experience on the relationship between perceived value and future behavior was not statistically significant, although it indicated a positive direction. These findings imply that authentic and emotionally meaningful culinary experiences can enhance tourist loyalty. Therefore, culinary destination managers should create dining experiences that are not only flavorful but also rich in cultural value and local narratives. This study contributes theoretically to the development of gastronomic tourism and serves as a strategic reference for designing culinary experiences that influence future tourist behavior.